Do children study longer depending on their parents’ level of engagement? An analysis of factors related to Brazilian students’ engagement - Esmeralda Correa Macana; Thamires Zaboto Mirolli; Ana Luíza Farage Silva; Lauana Rossetto Lazaretti; Lorenzo Luiz Bianchi; Gustavo Saraiva Frio; Marco Tulio Aniceto França (EconomiA)
Purpose – The purpose of this article is to investigate factors related to the time students spent on remote activities during the coronavirus (COVID-19) pandemic in 2020. Specifically, it analyzes whether the school’s relationship with the family and the guardians’ support are associated with longer study times for children and youth. Design/methodology/approach – This was performed using an ordered logit model on data from two waves of the survey Remote Education in the Perspective of Students and Their Families (PENP) with a nationally and regionally representative sample of Brazilian public school students. Findings – Results show the importance of contact between the school and the family and, to a greater extent, the direct support of parents or guardians. The odds of learners spending more hours studying increase 36% when schools provide guidance for parents and guardians; in turn, when they provide support for students during activities, these odds increase 144%. Originality/value – Moreover, students spend more time doing school activities in the later years of elementary school, high school and when they attend a state school.